VAT and Accounting Issues and Solutions in UAE - Zafarullah, Muhammad (International Journal of Social and Administrative Sciences, 2018)
Earlier the implementation of the VAT in UAE was the plan but now has become the reality in UAE. Most of the countries have the system of VAT or GST in accordance with the law of that country. In the initial stages these countries have also faced the challenges and have been solved easily. This article for the publication has been given for providing the overview of VAT and accounting issues that company and the firms will face in UAE. Along with defining the issues, the solution thereon has also been explained. It will help the businesses to implement the VAT successfully and manage the VAT related issues even after the implementation. There will be plethora of issues that the businesses will face in VAT registration. Detail has been given as to which approach of accounting shall be used for making the accounting entries under VAT. With these considerations the article is being presented and hopes it will be useful for the readers and users.